Projeto de lajes maciças de concreto com barras não metálicas - Godoi, Beatriz Pinheiro Furukawa (Universidade Federal de São Carlos, 2024)
Reinforced concrete slabs are very common elements across the various types of constructions. In general, their reinforcement is made up of steel bars, which posses high tensile strength, compensating for concrete’s deficiency in resisting such force. However, this material also has some desavantages, with its susceptibility to corrosion and high self-weight being two of the most prominent. Consequently, alternative materials are increasingly gaining traction in the market, which aimes for improved performance with reduced resource expenditure. In this context, glass fiber reinforced polymer (GFRP) bars have been under study as substitutes for steel reinforcement in concrete slabs due to their advantages such as low self-weight, high corrosion resistence, and versatility in geometry and machanical properties. Therefore, this work undertook the stuctural analysis of concrete slabs reinforced with GFRP bars. To achive this, slab modulations with different values of fck, spans, and environmental aggressiveness class were created. Based on these modulations, their dimensions were carried out, making it possible to compare the weight of reinforcement and concrete consumption between slabs reinforced with GFRP and conventional steel, aiming to analyze the possible reduction in the use of resources and the viability of this new material in the current market. As a result, it was found that slabs reinforced with fiberglass bars have similar values to slabs reinforced with steel, especially for smaller spans, which shows that they are a promising alternative for structural design.
Design of flat concrete slabs with non-metallic bars
Keywords: Barras de fibra de vidro; Barras não metálicas; Concreto armado; Lajes armadas; GFRP; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS